CCL2 produced by CD68+/CD163+ macrophages as a promising clinical biomarker of microscopic polyangiitis-interstitial lung disease. (26th January 2021) - Matsuda, Shogo; Kotani, Takuya; Kuwabara, Hiroko; Suzuka, Takayasu; Kiboshi, Takao; Fukui, Keisuke; Ishida, Takaaki; Fujiki, Youhei; Shiba, Hideyuki; Hata, Kenichiro; Shoda, Takeshi; Hirose, Yoshinobu; et al.
Abstract: Objectives: Microscopic polyangiitis (MPA) is often complicated by interstitial lung disease (ILD); however, biomarkers that can be used to diagnose and predict the progression of MPA-ILD have not been identified. In this study, we evaluated various serum biomarkers in MPA-ILD to assess their diagnostic and predictive performance. Methods: We enrolled 49 patients with anti-neutrophil cytoplasmic antibody (ANCA)+ MPA and 10 healthy controls, with 32 of the MPA patients also presenting ILD. The presence of ILD was assessed by high-resolution CT and evaluated by ground-glass opacity and fibrosis score. We compared 16 biomarker profiles among MPA-ILD patients, those without ILD, and healthy controls and extracted biomarkers with higher levels in MPA-ILD groups to determine correlations with disease activity and other biomarkers. Three lung biopsies were examined by haematoxylin-eosin staining and immunostaining. Results: Initial serum C–C motif chemokine ligand 2 (CCL2) levels were significantly higher in the MPA-ILD group than those of the MPA group, and were significantly higher in MPA-ILD patients 1 year after immunosuppressive therapy than those before treatment. Initial serum CCL2 levels positively correlated with an increased fibrosis score during the year after treatment and with initial serum platelet-derived growth factor levels. Immunohistochemical staining showed intense CCL2 signals in CD68+/CD163+ macrophages and metaplastic epithelial cells in MPA-ILD lungs. Conclusion: CCL2 is associated with MPA-ILD pathogenesis and suggested its potential efficacy as a useful marker for diagnosing and predicting MPA-ILD progression. Therefore, targeting CCL2 in alveolar CD68+/CD163+ macrophages might represent a therapeutic intervention in ANCA+ MPA-ILD.